Low-Dose Apatinib Combined With S-1 in Refractory Metastatic Colorectal Cancer: A Phase 2, Multicenter, Single-Arm, Prospective Study - Li, Ning; Deng, Wenying; Zhang, Guifang; Du, Yali; Guo, Yanwei; Ma, Yijie; Wei, Chen; Bie, Liangyu; Zhang, Chi; Song, Tao; Luo, Suxia; Fang, Baijun (Frontiers in Oncology, 2021)
Apatinib is an approved third-line treatment for metastatic gastric cancer and demonstrates good safety, tolerability, and efficacy in other advanced solid tumors. The aim of this prospective, single-arm, multicenter, phase 2 study was to assess the efficacy and safety of low-dose apatinib combined with S-1 in the treatment of refractory mCRC. Patients with refractory mCRC were enrolled and administered apatinib combined with S-1 until disease progression, patient decision to withdraw, or unacceptable toxic effects. The primary endpoint was investigator-evaluated progression-free survival (PFS) and the secondary endpoints were overall survival (OS), objective response rate (ORR), disease control rate (DCR). From December 2017 to December 2018, 30 patients were enrolled and 29 patients were eligible for the evaluation of efficacy and safety. The median PFS (mPFS) and OS (mOS) were 7.9 and 12.9 months, respectively. Exploratory analysis revealed that patients administered apatinib ≥ 140 days or S-1 ≥ 70 days achieved longer mPFS and mOS. Four patients achieved a partial response, 22 achieved stable disease, and three had progressive disease, attributing to an ORR of 13.79% and a DCR of 89.66%. Ten grade 3 adverse events were reported and the frequency of each grade 3 adverse event was less than 5%. No grade 4 side events were observed. These results indicated that apatinib combined with S-1 showed promising efficacy and manageable toxicity in patients with progressive mCRC after all standard therapies, making it a promising therapeutic option for mCRC treatment.